Less than slaves Jewish forced labor and the quest for compensation - Ferencz, Benjamin B. 1920-2023 (Harvard Univ.Pr., 1979)
Seven accounts of surviving Holocaust victims who Sued the companies that forced them and many others to work in slave labor camps. discusses the locating of the victims, the trials held in West Germany, and the decisions of the Court.
Keywords: Siemens Aktiengesellschaft; I.G. Farbenindustrie Aktiengesellschaft; Friedrich-Flick-Industrieverwaltung -- Düsseldorf; Konzentrationslager Buchenwald; Konzentrationslager Auschwitz; AEG-Aktiengesellschaft; Fried. Krupp -- Firma; Geschichte 1939-1945; Dwangarbeiders; Joden; Schadevergoeding; Tweede Wereldoorlog; Juden; Weltkrieg (1939-1945); Holocaust, Jewish (1939-1945); Holocaust, Jewish (1939-1945) -- Reparations; Slave labor -- Europe, Eastern; World War, 1939-1945 -- Claims; World War, 1939-1945 -- Conscript labor -- Europe, Eastern; Entschädigung; Zwangsarbeit; Wiedergutmachung; Konzentrationslager; Rüstungsindustrie; Zweiter Weltkrieg; Deutschland